Structural dynamics of the CROPs domain control stability and toxicity of Paeniclostridium sordellii lethal toxin - Yao Zhou; Xiechao Zhan; Jianhua Luo; Diyin Li; Ruoyu Zhou; Jiahao Zhang; Zhenrui Pan; Yuanyuan Zhang; Tianhui Jia; Xiaofeng Zhang; Yanyan Li; Liang Tao (Nature Communications, 2023)
Abstract Paeniclostridium sordellii lethal toxin (TcsL) is a potent exotoxin that causes lethal toxic shock syndrome associated with fulminant bacterial infections. TcsL belongs to the large clostridial toxin (LCT) family. Here, we report that TcsL with varied lengths of combined repetitive oligopeptides (CROPs) deleted show increased autoproteolysis as well as higher cytotoxicity. We next present cryo-EM structures of full-length TcsL, at neutral (pH 7.4) and acidic (pH 5.0) conditions. The TcsL at neutral pH exhibits in the open conformation, which resembles reported TcdB structures. Low pH induces the conformational change of partial TcsL to the closed form. Two intracellular interfaces are observed in the closed conformation, which possibly locks the cysteine protease domain and hinders the binding of the host receptor. Our findings provide insights into the structure and function of TcsL and reveal mechanisms for CROPs-mediated modulation of autoproteolysis and cytotoxicity, which could be common across the LCT family.